The Full Spectrum of Biomedical Informatics Education at Oregon Health & Science University - Hersh, W.R. (Methods of Information in Medicine, 2007)
Objectives: The growing use of health information technology in operational settings, along with the maturation of the discipline of biomedical informatics, requires reorganization of educational programs in the field. The objective of this paper is to provide a context and description of the biomedical informatics education program at Oregon Health & Science University.Methods: The details of the program are provided.Results: The paper describes the overall program and its component curricula.Conclusions: OHSU has developed a program that caters to the full spectrum of those who will work in the field, allowing education tailored to their career goals and needs. The maturation of Internet technologies also allow most aspects of the program to be delivered on-line. The informatics field must step up to the challenge of educating the best workforce to achieve our goals for the optimal use of HIT.
Keywords: Medical informatics; bioinformatics; health and biomedical informatics; education; distance learning